Pengaruh Persepsi Keramaian terhadap Loyalitas Wisatawan melalui Daya Tarik Wisata di Arunika Eatery - Popi Pebrianti; Pratama Putra , Gilang; Setia Lengkana , Anggi (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of perceived crowding on tourist loyalty, with tourist attraction as a mediating variable, at Arunika Eatery, Kuningan. Using a quantitative approach, data were collected from 260 respondents through an online survey and analyzed using PLS-SEM. The findings indicate that perceived crowding has a negligible direct effect on tourist loyalty but a moderate effect on tourist attraction. Tourist attraction strongly influences loyalty and significantly mediates the relationship between crowding and loyalty. These results emphasize the importance of managing perceived crowding and enhancing attraction quality to sustain tourist loyalty. Keywords: Perceived Crowding; Tourist Loyalty; Tourist Attractions; Overcrowding